Analysis of Nutritional Components, Functional Components and Bioactivity of Edible Dock - Xianxiu LI; Tao HE; Fan YANG; Chong WANG; Yi ZHOU; Ruyi SHA; Jianwei MAO (Shipin gongye ke-ji, 2023)
In order to explore the development and application of edible dock, the main nutrients and functional components contents were measured, and the antioxidant and hypoglycemic activities were evaluated by measuring the free radical scavenging ability, reducing power and α-glucosidase inhibitory of extract from edible dock. The results showed that the value of total protein reached about 34.70 mg/100 mg (dry weight), the ratios of essential amino acids and medicinal amino acids to total amino acids were respectively 45% and 65%, and the score of amino acid ratio coefficient (SRC) was over 68, indicating that the edible dock was a kind of plant of high nutritional value. The contents of total phenol, total flavonoid and the specific activity of superoxide dismutase were 11.35 mg GAE/g (dry weight), 3.56 mg RE/g (dry weight) and 15.24±3.40 U/mg pro, respectively. Malic acid and oxalic acid were the main organic acid in edible dock (~89.24%). The values corresponding to the extract concentration required to scavenge 50% (IC50) of 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical and 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radical were respectively 0.465 mg/mL and 0.066 mg/mL, and the extract concentration providing reducing power (absorbance) of 0.5 (IC0.5) was about 0.528 mg/mL, which indicated that the edible dock possessed good antioxidant activity. Moreover, the extract of edible dock significantly inhibited α-glucosidase activity in experimental ranges, thus proving its favorable hypoglycemic activity. The above results can enrich the scientific research of edible dock and provide the theoretical foundation for its further development and utilization.